Nuclear ROK and US’ Military Retrenchment: Changes of Approach toward Korean Peninsula Crisis - Fathur Rahman, Dzulfikar (Indonesian Perspective, 2017)
North Korea has conducted sixth nuclear device tests by 2017. But the United States and South Korea persist on their current approach, that is pressure and sanction. The ways in which the United States and South Korea manage the Korean Peninsula crisis beg us to rethink, since the objective thereof, namely denuclearization, has not come into fruition. There are three problems to discuss. First, why North Korea keeps developing its nuclear weapons program. Second, why the current approach of the United States and South Korea seemingly fails. Third, what kind of changes the United States and South Korea need to have. This article argues, South Korea needs to acquire and develop its own nuclear weapons, and the United States needs to perform military retrenchment by retracting United States Forces Korea from the Peninsula. To examine the argument, neorealist theory, Waltz’s proposition on the further spread of nuclear weapons, and theory of military retrenchment, all provide necessary framework.Keywords: Korean Peninsula crisis, nuclear ROK, US military retrenchment, neorealist theory